2022
DOI: 10.3389/fmicb.2022.1027785
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of Staphylococcus aureus using a novel multienzyme isothermal rapid amplification technique

Abstract: Staphylococcus aureus is a common pathogen that causes various infections. Therefore, it is crucial to develop a fast and easy detection method for diagnosing and preventing S. aureus infections. In this study, MIRA assay was developed and validated (specificity; 100%) for the detection of S. aureus with nuc as the target gene. The reaction temperature and reaction time were then optimized, and the best reaction was at 40°C, 20 min. The assay could detect S. aureus in only 25 min. Additionally, the limit of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…However, recent studies using the MIRA assay have reported that the positive test line could be observed after 5 min for S. eriocheiris, A. baumannii, and Streptococcus agalactiae [33,34,36]. Since the MIRA assay applies a different source of recombinase (Streptomyces azure recA, SC-recA) compared to the RPA assay that uses the RecA/Rad 51 ortholog of bacteriophage T4, T4 UvsX, this may result in different incubation times for amplification [31].…”
Section: Optimization Of Mira-lfd To Amplify Tlh Trh and Tdh Genesmentioning
confidence: 99%
See 3 more Smart Citations
“…However, recent studies using the MIRA assay have reported that the positive test line could be observed after 5 min for S. eriocheiris, A. baumannii, and Streptococcus agalactiae [33,34,36]. Since the MIRA assay applies a different source of recombinase (Streptomyces azure recA, SC-recA) compared to the RPA assay that uses the RecA/Rad 51 ortholog of bacteriophage T4, T4 UvsX, this may result in different incubation times for amplification [31].…”
Section: Optimization Of Mira-lfd To Amplify Tlh Trh and Tdh Genesmentioning
confidence: 99%
“…Previous studies on the detection of V. parahaemolyticus using RPA assays have reported detection limits ranging from 76 to 2 CFU of bacterial culture and 10 pg of genomic DNA [27][28][29][30]. More recently, MIRA assays for various pathogens have shown detection limits ranging from 760 to 6 CFU of bacterial culture and ranging from 97 pg to 64 fg of genomic DNA [31,33,34,[36][37][38].…”
Section: Evaluation Of the Sensitivity And Specificity Of The Tlh Trh...mentioning
confidence: 99%
See 2 more Smart Citations
“…MIRA has been widely applied in diagnostic settings due to its advantages such as simplicity, rapidity, and sensitivity. It has been used for the detection of various pathogens, including bacteria and viruses (12,13).However, MIRA also has some limitations. One major drawback is the potential for nonspecific amplification, leading to false-positive results.…”
Section: Introductionmentioning
confidence: 99%